CREATING AN INTELLIGENT MECHATRONIC MODULE WORKING WITH ROBOTIC MANIPULATORS ON MACHINE BUILDING LINES (American Journal of Technology and Applied Sciences, 2025)
This article explores the development of an intelligent mechatronic module designed to synchronize the operation of robotic manipulators in machine-building production lines. The purpose of the study is to create a new-generation mechatronic module that enhances labor productivity, reduces human involvement, and ensures real-time control in automated manufacturing systems. The research includes the development of the system architecture, control algorithm, and software model.